2005
DOI: 10.1002/lsm.20183
|View full text |Cite
|
Sign up to set email alerts
|

A study of the effects of phototherapy dose interval on photobiomodulation of cell cultures

Abstract: Cellular response to dose frequency varies. More frequent treatments (2/24 hours) increased metabolism and proliferation in both cell lines. Further investigation of dose fractionation in phototherapy is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 11 publications
2
32
0
5
Order By: Relevance
“…Different photobiomodulatory effects have been described depending upon the specific cell lines and species being investigated. Our laboratory demonstrated that cell proliferation and metabolism in vitro can be influenced by varying the dose frequency or treatment interval of the PBMT (17). We have also demonstrated this same phenomenon as regards wound healing in a murine pressure ulcer model (18).…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…Different photobiomodulatory effects have been described depending upon the specific cell lines and species being investigated. Our laboratory demonstrated that cell proliferation and metabolism in vitro can be influenced by varying the dose frequency or treatment interval of the PBMT (17). We have also demonstrated this same phenomenon as regards wound healing in a murine pressure ulcer model (18).…”
mentioning
confidence: 52%
“…Light at this wavelength is known to be absorbed by cytochrome C oxidase and other molecules, stimulating ATP synthesis and affecting ROS production, among numerous other activities at the cellular, tissue and whole organism level (16). The caveat however is that the light dose and dose rate are important and that all cell and tissues are not equally responsive to photoradiation (16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Holder et al (3) used a primary culture of rodent dental pulp, in which fibroblasts, stem cells, endothelial and other cells are present, whereas in the present study, an immortalized culture of odontoblast-like cells were used. The sensitivity of these cells is different from cells in a primary pulp culture (21). The difference in sensitivity between cell cultures may be related to the intrinsic characteristics of each cell, as well as to the process of immortalization of the cell culture (22).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, since the dose-response effect varies according to the set of irradiation parameters (21), it may be suggested that a higher frequency of exposure of MDPC-23 cells to LED exceeded the threshold of biological tolerance of these cells, leading to a reduction in their metabolism. Previous studies that evaluated the bio-stimulatory effects of light sources have observed such biphasic effect (1,15,20).…”
Section: Discussionmentioning
confidence: 99%